Antitumor activities of Grifola frondosa (Maitake) polysaccharide: A meta-analysis based on preclinical evidence and quality assessment. (15th November 2021) - Zhao, Fei; Guo, Zhong; Ma, Zhong-Ren; Ma, Ling-Li; Zhao, Jin
Abstract: Ethnopharmacological relevance: The antitumor effects of Grifola frondosa /maitake polysaccharide (GFP) have been reported in many preclinical studies, especially in vivo experiments. The present meta-analysis aimed to provide an in vivo evidence and theoretical basis for future clinical trials by assessing the efficacy and underlying mechanisms of GFP in tumor treatment. Materials and methods: English and Chinese databases were examined to include animal experiments to study the antitumor activity of GFP. Literature screening, data extraction, and meta-analysis were conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. In addition, the Systematic Review Center for Laboratory animal Experimentation (SYRCLE) risk of bias (RoB) tool was used to assess the risk of bias of the included animal studies. Results: Potentially relevant studies (442) were identified, and finally 24 eligible studies (all in English) were included. The meta-analysis revealed that GFP has significant effects in inhibiting tumor growth (high dose: mean difference (MD) = −1.34, 95% confidence interval (CI) = [−1.73, −0.95]; low dose: MD = −5.68, 95% CI = [−7.27, −4.09]), improving tumor remission rate (odds ratio = 25.59, 95% CI = [9.08, 72.11]), and enhancing immune function in both cellular (CD4 + T cell percentage: MD = 3.03, 95% CI = [1.16, 4.90]; CD8 + T cell percentage: MD = 1.10, 95% CI = [-0.29, 2.49]) and humoral immunity (MD and [95% CI] of interleukin (IL)-2, IL-12 and tumor necrosis factor-α were 7.86 [6.29, 9.44], 35.95 [5.18, 66.72], and 10.03 [8.71, 11.36], respectively), and the differences between the two groups of the above indicators were statistically significant (all P  < 0.01) except CD8 + T cell percentage. Additionally, the quality of the included studies was not high, and the risk of bias mainly concentrated on selection, detection, and reporting biases. Conclusion: GFP is a potential candidate for tumor treatment and clinical trials. Trial registration: The review protocol for this study was registered with the PROSPERO database before beginning the review process (CRD42018108897). Graphical abstract: Image 1